VEGFA, VEGFR1, VEGFR2 serum and cerebrospinal fluid concentration in patients with acute leukemia - E. I. Zakharko; V. N. Dvirnyk; Yu. A. Chabaeva; D. G. Drokova; E. B. Rybkina; K. A. Lavrishinets; A. V. Bulgakov; M. N. Panasenko; Z. T. Fidarova; I. A. Lukianova; O. A. Aleshina; S. M. Kulikov; et al. (Онкогематология)
Background. Vascular endothelial growth factor A (VEGFA) is one of the most important factors for regulation of hematopoietic stem cells differentiation. It is involved in leukemogenesis and central nervous system (CNS) damage in acute leukemia. According to the literature, the VEGFA production by blast cells is increased, but the values of serum concentration and the associations with CNS involvement are contradictory.Aim. evaluate the VEGFA, VEGFR1, VEGFR2 concentration in serum and cerebrospinal fluid of patient with different types of acute leukemia in disease onset and during treatment.Materials and methods. The concentration of VEGFA in serum and cerebrospinal fluid was studied in 74 primary patients with acute leukemia. The comparison group consisted of 67 healthy donors. VEGFR1, VEGFR2 were studied in serum and cerebrospinal fluid in 34 patients at the onset of the disease. The comparison group consisted of 10 healthy donors. For the analysis, an enzyme immunoassay was used on a semi-automatic Personal Lab analyzer (Adaltis) and Affymetrix eBioscience human VEGF-A Platinum ELISA reagents.Results. Serum VEGFA concentration was statistically significantly lower in acute leukemia patients than that of donors (median 149.78 and 432.19 pg/ml respectively; p <0.0001). Factor deficiency was significantly more pronounced in patients with blastemia (p <0.015). During antitumor therapy, there was a tendency to increase the amount of the factor in the blood serum. Serum concentration of soluble VEGFR2 was also lower in patients than that of donors (6949.9 and 8795.9 pg/ml respectively; p = 0.0026). For concentration of VEGFR1 such deviations were not found. The concentrations of VEGFR1 and VEGFR2 in serum were higher than in cerebrospinal fluid (p <0.0001), while VEGFR1 showed a positive correlation between serum and cerebrospinal fluid concentrations. the concentration of VEGFR1 in the cerebrospinal fluid was significantly lower in patients with B-lymphoblastic leukemia/lymphoma compared to other types of leukemia.Conclusion. the concentration of VEGFA in serum decreases in patients with blastemia, this may indicate a lack of secretion and excessive consumption of the factor by blast cells with a decrease in the proportion of leukocytes that normally secrete the factor. In the cerebrospinal fluid, the concentrations of VEGFR1 and VEGFR2 are lower than in serum, with the lowest values being found in patients with B-lymphoblastic leukemia/lymphoma, but no relationship with the development of CNS involvement was found.